1793 Effect of Chest Compressions on Mask Leak During Neonatal Resuscitation: A Manikin Study. (October 2012) - Schwaberger, B; Schmölzer, GM; Binder, C; Müller, W; Urlesberger, B; Pichler, G
Abstract : Background: Chest compressions during neonatal resuscitation are an infrequent event during neonatal resuscitation. Objectives: To investigate if chest compressions (CC) during simulated neonatal cardio-pulmonary resuscitation affect percentage of mask leak. Methods: 21 neonatal staff members (11 Neonatal nurses, 10 Neonatologists) delivered positive pressure ventilation (PPV) to a modified, leak-free manikin via face mask using a Neopuff T-piece device. After 90 seconds of PPV-only (baseline) an assistant provided chest compressions (CC) at a ratio of 3:1 chest compressions to inflations for further 90 seconds ( PPV + CC ). Mask leak was measured with a Florian respiratory function monitor . Results between PPV-only and PPV + CC were compared using dependent t-test for paired samples. Results: A total of 2726 ventilations and 3058 chest compressions were analyzed. Overall the mean (SD) mask leak during PPV-only and PPV + CC was similar 35 (±30)% versus 40 (±33)% (p=0.2). However, in the neonatal nurse group mask leak significantly increased from 27 (±26)% in the PPV-only group to 43 (±35)% in the PPV + CC group (p=0.04). In comparison, mask leak was similar in the neonatologist group in the PPV-only and PPV + CC group 42 (±33)% and 37 (±34)% (p=0.65), respectively. Conclusions: Overall, mask leak did not change once chest compressions were started. However, mask leak significantly increased in the neonatal nurse group once chest compression were provided, but remained similar in the neonatologist group.